MUDAS DE EUCALIPTO EM BANDEJAS DE TUBETES COLORIDAS E APLICAÇÃO DE BIOINSUMO À BASE DE MICROALGAS - BARRETO, Andressa Fernanda Santos; COSTA, Edilson; ROCHA, Alana Silva; RODRIGUES, Nicolly Queiroz (ANAIS DO ENIC, 2025)
-